Exploring Financial Awareness among Undergraduate Students at Hodeida University in Yemen - Ebrahima, Mohammed M. Sulaiman; Akhtar, Asif; Thabit, Ali; Khaled, Amgad S. D (Eastasouth Institute, 2024)
In a country like Yemen, where people exist on meager incomes and struggle to make ends meet, poverty is widespread. There is an urgent need to maintain, administer, and set aside funds for emergencies. This study aims to explore the Level of Financial Awareness and financial knowledge among Undergraduate Students in Yemen. Students attending educational institutions of a higher level are expected to be responsible for managing their expenses and they have a high level of financial awareness. The study relied on primary data collected from a randomly selected sample of people. A total of 218 students at Hodeida University in Yemen were randomly selected to participate in the study. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The results show that the level of ﬁnancial awareness among Undergraduate Students at Hodeida University in Yemen is high, and also observed that males, on average, have financial knowledge more than females. In this light, the research adds to the body of information on financial awareness by illustrating the significance of financial literacy and access to financial knowledge among Yemeni undergraduate students. Finally, we strongly recommend academics, teachers, legislators, financial institutions, and governments make financial education a mandatory element of every school's curriculum, regardless of the level.